Mesenchymal stem cell expression of stromal cell‐derived factor‐1β augments bone formation in a model of local regenerative therapy. Issue 2 (28th October 2014) - Herberg, Samuel; Kondrikova, Galina; Hussein, Khaled A.; Johnson, Maribeth H.; Elsalanty, Mohammed E.; Shi, Xingming; Hamrick, Mark W.; Isales, Carlos M.; Hill, William D.
Abstract Bone has the potential for spontaneous healing. However, this process often fails in patients with co‐morbidities requiring clinical intervention. Numerous studies have revealed that bone marrow‐derived mesenchymal stem/stromal cells (BMSCs) hold great potential for regenerative therapies. Common problems include poor cell engraftment, which can be addressed by irradiation prior to transplantation. Increasing evidence suggests that stromal cell‐derived factor‐1 (SDF‐1) is involved in bone formation. However, osteogenic contributions of the beta splice variant of SDF‐1 (SDF‐1β), which is highly expressed in bone, remain unclear. Using the tetracycline (Tet)‐regulatory system we have shown that SDF‐1β enhances BMSC osteogenic differentiation in vitro. Here we test the hypothesis that SDF‐1β augments bone formation in vivo in a model of local BMSC transplantation following irradiation. We found that SDF‐1β, expressed at high levels in Tet‐Off‐SDF‐1β BMSCs, augments the cell‐mediated therapeutic effects resulting in enhanced bone formation, as evidenced by ex vivo μCT and bone histomorphometry. The data demonstrate the specific contribution of SDF‐1β to BMSC‐mediated bone formation, and validate the feasibility of the Tet‐Off technology to regulate SDF‐1β expression in vivo. In conclusion, SDF‐1β provides potent synergistic effects supporting BMSC‐mediated bone formation and appears a suitable candidate for optimization of bone augmentation in translational protocols. Published 2014. This article has been contributed to by US Government employees and their work is in the public domain in the USA. J Orthop Res 33:174–184, 2015.